2018
DOI: 10.1136/archdischild-2017-314206
|View full text |Cite
|
Sign up to set email alerts
|

Treatment thresholds for intervention in posthaemorrhagic ventricular dilation: a randomised controlled trial

Abstract: There was no significant difference in the primary composite outcome of VP shunt placement or death in infants with posthaemorrhagic ventricular dilatation who were treated at a lower versus a higher threshold for intervention. Infants treated at the lower threshold received more invasive procedures. Assessment of neurodevelopmental outcomes will provide further important information in assessing the risks and benefits of the two treatment approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 26 publications
3
69
0
Order By: Relevance
“…There is one trial using a drainage and fibrinolytic approach (DRIFT Trial) that has shown some potential benefits on the neurological outcome, but data were inconclusive due to follow-up problems and other methodological issues (Luyt et al, 2019). There is also a management trial (ELVIS TRIAL) comparing early versus late approach in lumbar tapping and rickham insertion, which is underway (de Vries et al, 2019). It is known that blood rapidly accumulates within the ventricles following IVH, and this leads to disruption of normal cerebrospinal fluid flux and can cause obstruction and increased local tissue pressure as one of the potential etiological mechanisms (Klebe et al, 2020).…”
Section: Intraventricular and Intraparenchymatous Hemorrhagesmentioning
confidence: 99%
“…There is one trial using a drainage and fibrinolytic approach (DRIFT Trial) that has shown some potential benefits on the neurological outcome, but data were inconclusive due to follow-up problems and other methodological issues (Luyt et al, 2019). There is also a management trial (ELVIS TRIAL) comparing early versus late approach in lumbar tapping and rickham insertion, which is underway (de Vries et al, 2019). It is known that blood rapidly accumulates within the ventricles following IVH, and this leads to disruption of normal cerebrospinal fluid flux and can cause obstruction and increased local tissue pressure as one of the potential etiological mechanisms (Klebe et al, 2020).…”
Section: Intraventricular and Intraparenchymatous Hemorrhagesmentioning
confidence: 99%
“…4 After the use of temporizing methods, overall conversion to a permanent shunt varies from 20-65% depending on the time of onset of the intervention. 5 Given the high rates of infection, dysfunction and life-long dependence after VP-shunt insertion, it would be beneficial if a treatment could reduce the risk of shunt requirement. 6,7 Removing the hemorrhagic CSF by lumbar punctures or taps from a ventricular reservoir may reduce the need for VP-shunt placement, since removal of CSF that contains blood components, protein, and cytokines might re-establish normal CSF circulation.…”
Section: Introductionmentioning
confidence: 99%
“…VI and AHW values greater than normal (VI >2 + SD and AHW > 6) have been used as cutoffs for surgical intervention [49]. Other groups have compared this typical PHVD cutoff to a higher one (VI > 97th percentile + 4 mm and AHW > 10 mm) [22]. An increase in AHW may be a more sensitive marker for early enlargement; it is seen clinically as the rounding of the frontal horns.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have compared different magnitudes of early treatment thresholds and found no long-term developmental outcome differences [22]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation